İslam inançları açısından din-dünya ilişkisi - Kır, Hülya (My University, 2004)
İSLÂM İNANÇLARI AÇISINDAN DİN-DÜNYA İLİŞKİSİ Hazırlayan Hülya KIR İslâm İnançları Açısından Din-Dünya İlişkisi adlı ısından din fenomeninin insan hayatıyla ilişkisini anlamaya yönelik bir çalışmanın ürünüdür. Öncelikle ilişkinin iki ucu din ve dünya hayatının İslâm dini ölçeğinde nasıl anlaşıldığı ifadelendirilmiş, ikinci olarak da kurumsal kimliğiyle bu dininin toplumsal hayatla iletişimi ortaya konmuştur. Metin üç ana bölümden oluşmaktadır: Birinci bölümde İslâm'ın ortaya çıktığı sosyokültürel ortamda dinin hayatla ilişkisi okunmuş ve bu çerçevede İslâm öncesi yakın tarih, târihî, sosyokültürel ve dînî yaşantı açılarından incelenmiştir. Son olarak o günkü toplumun İslâm dinine itiraz noktaları tespit edilmek suretiyle yeni dinin hayata dair iddiaları belirlenmeye çalışılmıştır. İkinci bölüm tezin asıl çatısını oluşturmaktadır. Bu bölümde din-dünya ilişkisinin teolojik temelleri ele alınmaktadır. İslâm dininin ilk ana kaynağı Kur'ân-ı Kerim'de ve Hz. Muhammed'in nübüvvet (peygamberlik) tecrübesinde bu ilişkinin nasıl tanımlandığı örneklerle izah edilmiştir. Bölümün sonunda ise bu iki kaynağa yönelik modern bazı bakış açıları ortaya konarak meselenin güncelliğine gönderme yapılmıştır. Üçüncü ve son bölümde ise konunun Kelâm disiplininin târihî arka plânında ne şekilde tartışıldığı ele alınmaktadır. Bu bağlamda insanın Yaratıcı karşısında nasıl tanımlandığı, iradesi, fiillerine yetkinliği, akıl-vahiy ilişkisi, inanç-davranış ilişkisi gibi başlıklar tartışılmış ve Yaratıcının insana bıraktığı alan tespit edilmeye çalışılmıştır. Bu bölümde dinin dünya hayatıyla ilişkisi, dinin insanla ilişkisi çerçevesinde tartışılmıştır. RELIGION-WORLD RELATIONSHIP FROM THE ISLAMIC BELIEF PERSPECTIVE Doctorate Thesis Prepared by Hülya KIR The doctorate thesis entitled Religion-World Relationship from the Islamic Belief Perspective, is a product of a study aimed at understanding the relationship between religion as a phenomenon in Islamic terms and human life. First of all, how the two ends of the relationship; religion and worldly life is understood from Islam religion's perpective is stated and secondly the relationship of this religion with its institutional identity, and social life is put forward. The text comprises of three main parts: In the first part, a detailed research was done on the relationship between religion and life in the socio-cultural environment where Islam was born and in this frame, recent history before Islam was examined considering the historical and socio-cultural aspects and life pertaining to religion. Finally, the new religion's claims related to life were tried to be determined while the society in question was analyzed to find out their points of objection considering Islam religion. The second part stands to be the main framework for the thesis. The theological foundation of religion-world relationship is the matter of concern throughout this part. How this relationship is defined in Quran, the very first source of Islam, and the experience of Muhammad's prophethood is explained in detail. On the otherhand, at the end of the part, certain modern viewpoints related to these two sources are stated so as to refer the subject's actuality. In the third and the last part, how the subject is discussed in the historical background of theological discipline is dealt with. In this context, certain points such as how the human being is defined before the Creator, his will, the Creator's influence on his actions, reason-revelation relationship, belief-behaviour relationship are discussed and the space left to humans by the Creator is tried to be determined. In this part, the relationship between religion and worldly life is subject to discussion with close reference to religion-human life relationship.
Keywords: Din; İslam Dini; İslamiyet; Kelam; Tefsir ve tefsir ilmi